A Revolution in Health Care Sector Through Data Sciences (Medico Legal Update, 2020)
Healthcare industry is undergoing a digital transformation. There is lot of work which is happening thatleverages the newer technologies in the healthcare industry. Technological advancements will be driverfor change for future ready health care industry. Health care industry, now understands the role of digitaltechnology platforms and has started embracing it to be future ready.Digital transformation in health care industry shall be another milestone in patient care and hospitalmanagement. Changing mind-set of care givers and customers will be a challenge for all players to thinkdifferently. Emergence of disruptive technology in health care industry has potential scope to provide errorfree services worldwide. This is a qualitative study in which challenges and opportunities of Technology inHealth Care Industry will cover.